Possible future scenarios for CARDI - Paul, Compton L. (CARDI [St. Augustine]TT, 2001)
Provides three scenarios regarding the future of CARDI viz. the strategic framework 2001-2006; the reduced option for CARDI; and, the PROCICARIBE option.